The trophic and spatial ecology of juvenile porcupine rays Urogymnus asperrimus at the remote St. Joseph Atoll - Elston, Chantel (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2016)
Little information exists for the widely occurring but rare porcupine ray Urogymnus asperrimus. This is a concern given that it is a vulnerable species and likely plays an important ecological role in tropical atoll ecosystems. The aims of this thesis were to investigate the trophic and spatial ecology of juvenile porcupine rays within the St. Joseph Atoll, which is hypothesized to be functioning as a nursery for this species. Specific objectives were to determine i) the dietary composition and resource selectivity displayed by juvenile porcupine rays, ii) residency to the atoll, space use, and seasonality in movements, and iii) whether environmental factors affect short-term movements. Gastric lavage was used to collect stomach contents from 55 juveniles and sediment samples were collected. Thirteen juveniles were implanted with acoustic transmitters and monitored for a year by an array of 88 acoustic receivers situated in and around the St. Joseph Atoll. Porcupine rays appeared to be generalist and opportunistic feeders, foraging predominantly on annelids with the highest environmental availability. Polychaetes of the family Capitellidae were the most important prey item (Index of Importance = 35%). Rays only fed on deep infaunal prey, likely because of their foraging behaviour, suggesting they may influence this community. There was a size-related shift in the crustacean families consumed. The tagged rays displayed high residency to the atoll (mean residency index of 64%) and restricted movements, with small core use and activity space areas (mean of 0.5kmÂ² and 3kmÂ² respectively) and the majority of detections were recorded within 1km of their tagging locations. The rays favoured the sand ats where 88% of detections occurred. Transient use of the lagoon and fringe reef peaked in the north-west monsoon season, indicating a seasonal usage of these habitats. The effects of temperature and water depth on movements were manifested as diel and tidal cyclical patterns in presence. Evidence illustrates that the St. Joseph Atoll constitutes an important nursery for this species, which has been declared a Marine Protected Area. A major determinant behind the dependence of this nursery habitat is related to predator avoidance. Thermoregulatory behaviours were identified, suggesting that this species is vulnerable to climate change.
Keywords: Uncatalogued